2001
DOI: 10.1097/00005392-200101000-00062
|View full text |Cite
|
Sign up to set email alerts
|

The Response of Balanitis Xerotica Obliterans to Local Steroid Application Compared With Placebo in Children

Abstract: Applying a potent topical steroid affects improvement in balanitis xerotica obliterans in the histologically early and intermediate stages of disease, and may inhibit further worsening in the late stage.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
82
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(85 citation statements)
references
References 13 publications
0
82
0
3
Order By: Relevance
“…Because BXO had been regarded as an adult disease for a long time, current literature differs from older literature regarding the incidence of BXO in children [7]. Recently, researchers have indicated that BXO may be an etiological factor for up to 20% of phimosis cases in boys [8,9,10]. This new data indicates a significantly higher incidence of BXO than that previously reported.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…Because BXO had been regarded as an adult disease for a long time, current literature differs from older literature regarding the incidence of BXO in children [7]. Recently, researchers have indicated that BXO may be an etiological factor for up to 20% of phimosis cases in boys [8,9,10]. This new data indicates a significantly higher incidence of BXO than that previously reported.…”
Section: Introductionmentioning
confidence: 84%
“…Data indicates that the application of a potent topical steroid cream results in improvement in BXO in the histopathologically early and intermediate stages of the disease. Furthermore, topical steroid therapy has been reported to slow down the progression of the disease [6,9,17]. Circumcision is the treatment of choice for clinically suspected BXO, because this procedure may be curative.…”
Section: Discussionmentioning
confidence: 99%
“…The term lichen sclerosus et atrophicans describes a chronic inflammatory skin disorder, whereas the term balanitis xerotica obliterans describes the occurrence of lichen sclerosus et atrophicans on the penile skin. The prevalence of penile lichen sclerosus et atrophicans is in the range of 1/300 to 1/1,000 in adults, but in children it is probably higher (10-14% of children phimosis scheduled for circumcision) [7] .…”
Section: Introductionmentioning
confidence: 99%
“…3 While most of the patients who present with the same are asymptomatic, a small proportion of children does have symptoms like ballooning, dribbling, balanoposthitis or even urinary tract infections. 4 Older children may present differently with pain during erection.…”
Section: Introductionmentioning
confidence: 99%